High-fat-diet impaired mitochondrial function of cumulus cells but improved the efficiency of parthenogenetic embryonic quality in mice. Issue 4 (4th July 2018) - Li, Jingjing; Wang, Shuang; Wang, Bo; Wei, Hao; Liu, Xin; Hao, Jun; Duan, Yanping; Hua, Jinlian; Zheng, Xiaomin; Feng, Xiuliang; Yan, Xingrong
ABSTRACT: Global human health has been compromised by high-fat diets. This study aimed to investigate the relationship between a high-fat diet and parthenogenetic embryo quality. Mice fed a high-fat or a normal diet was used as treated or control groups, respectively. Estradiol (E2 ), total cholesterol (TC) and total triglyceride (TG) were detected by Enzyme-Linked ImmunoSorbent Assay (ELISA). Cumulus-oocyte complexes (COCs) were collected from the mice in the treated and control groups. The ultrastructure of COCs, the expression level of genes involved in mitochondrial and nuclear functions in cumulus cells and oocytes quality were evaluated with transmission electron microscopy, real-time quantitative polymerase chain reaction (RT-PCR) and artificial parthenogenesis, respectively. The results showed that the efficiency of parthenogenetic embryonic development in vitro was significantly higher in the treated group than in the control group ( p < .05). The expression level of genes involved in mitochondrial function was lower in cumulus cells from the treated group than that from the control group ( p < .05). The estradiol and cholesterol level in the serum and the expression level of P450 arom were higher in the treated group than the control group ( p < .05). The reactive oxygen species (ROS) level was higher in culumus cells from the treated group than the control group, while the mitochondrial membrane potential was lower in cumulus cells from the treated group ( p < .05). Accumulation of lipid droplets was only in cumulus but in oocyte, the results demonstrated that mitochondrial functions were impaired by a high-fat diet, but parthenogenetic embryonic development in vitro was improved, in controllable range of damage for the body.